(untitled) - Esther NAVARRO-ESCOBAR; Pilar BACA; María Paloma GONZÁLEZ-RODRÍGUEZ; María Teresa ARIAS-MOLIZ; Matilde RUIZ; Carmen María FERRER-LUQUE (University of São Paulo, 2013)
ObjectiveTo assess the influence of final irrigation protocols with chlorhexidine in the coronal leakage of Enterococcus faecalis in filled root canals.Material and MethodsSeventy single-root canals from extracted teeth were prepared using ProTaper instruments. The irrigation protocol accomplished an alternating irrigation with 5 mL of 2.5% sodium hypochlorite (NaOCI) and 17% EDTA between each file. The teeth were randomly divided into four experimental groups (n=15) according to the final irrigation regimen: group 1, without final irrigation; group 2, irrigation with 10 mL 2.0% chlorhexidine (CHX); group 3, with a final application of EC40™; and group 4, irrigation with the combination (1:1) of 0.2% CHX + 0.1% cetrimide (CTR). All the teeth were mounted in a two-chamber apparatus and the coronal access was exposed to E. faecalis. The presence of turbidity in the BHI broth over a period of 180 days was observed. The Friedman test was used for statistical analysis.ResultsEC40™ varnish showed the least leakage at 180 days, and was statistically similar to 2% CHX. No significant differences were observed between the group without final irrigation and the 2% CHX group or 0.2% CHX + 0.1% CTR.ConclusionsIn this ex vivo study, EC40™ showed the longest delayed coronal leakage of E. faecalis, although without significant differences from 2% CHX.